Improving Self-Efficacy and Physical Self-Reliance of Patients with Pulmonary Tuberculosis through Mindfulness - Noorratri, Erika Dewi; Margawati, Ani; Dwidiyanti, Meidiana (Department of Nursing, Faculty of Medicine, Diponegoro University, 2016)
Background: Patients with pulmonary tuberculosis (TB) have a low level of medication adherence due to long care terms, side effects of medication and self-awareness. This awareness can be promoted by practicing mindfulness.Purpose: The study aimed to analyze the improvement of self-efficacy and self-reliance of patients with pulmonary TB through mindfulness intervention.Methods: This study employed a quasi-experiment with pre-post-test group design. The sampling technique was purposive sampling with 19 patients in the intervention group and 19 patients in the control group. The intervention given was mindfulness. The data were analyzed using the Wilcoxon and delta tests.Results: The study showed an increase of self-efficacy and physical self-reliance in patients in the intervention group with a p-value of <0.05. In the intervention group, there were differences in the activities of taking medication, eating, sleeping, preventing infection, practicing and coping with physical symptoms before and after the intervention. Furthermore, the patients in the intervention group also showed differences in their increased confidence to recover. Mindfulness intervention provided good effects on the patients in the intervention group as it helped them develop more awareness. Conclusion: Mindfulness intervention improved the self-efficacy and physical self-reliance of the patients with pulmonary TB. This study recommends that nurses should apply mindfulness to promote the awareness of the patients.Â